Increased level of arginase activity correlates with disease severity in HIV-seropositive patients - Cloke, Thomas; Garvey, L.; Choi, B.-S.; Abebe, T.; Hailu, A.; Hancock, M.; Kadolsky, U.; Bangham, C. R. M.; Munder, Markus; Müller, I.; Taylor, G. P.; Kropf, P. (The journal of infectious diseases, 2010)
Infection with human immunodeficiency virus (HIV) results in a chronic infection that progressively impairs the immune system. Although depletion of CD4(+) T cells is frequently used to explain immunosuppression, chronicity of infection and progressive loss of CD4(+) T cells are not sufficient to fully account for immune dysregulation. Arginase-induced l-arginine deprivation is emerging as a key mechanism for the down-regulation of immune responses. Here, we hypothesized that the level of arginase activity increases with disease severity in HIV-seropositive patients. We determined the levels of arginase activity in peripheral blood mononuclear cells from HIV-seropositive patients and uninfected control participants. Our results show that peripheral blood mononuclear cells from HIV-seropositive patients with low CD4(+) T cell counts expressed statistically significantly higher levels of arginase activity, compared with patients with high CD4(+) T cell counts or uninfected control participants. Furthermore, we found a statistically significant correlation between high level of arginase activity and high viral load in HIV-seropositive patients.